2013
DOI: 10.1002/jpln.201200393
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term tillage effects on the distribution of phosphorus fractions of loess soils in Germany

Abstract: Different tillage systems may affect P dynamics in soils due to differently distributed plant residues, different aggregate dynamics and erosion losses, but quantitative data are scarce. Objectives were to investigate the effect of tillage on the availability of P in a long-term field trial on loess soils (Phaeozems and Luvisols) initiated from 1990 to 1997. Four research sites in E and S Germany were established with a crop rotation consisting of two times winter wheat followed by sugar beet. The treatments w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 33 publications
1
12
2
Order By: Relevance
“…Other authors found, on the contrary, a clear stratification of P avail in no-till systems compared to inversion tillage with the highest values in the upper 5 cm of the no-till treatments [38]. As soil disturbance was more intensive in our study compared to the no-till treatments of Piegold et al [38], such clearly pronounced stratification could not occur.…”
Section: Meancontrasting
confidence: 79%
See 1 more Smart Citation
“…Other authors found, on the contrary, a clear stratification of P avail in no-till systems compared to inversion tillage with the highest values in the upper 5 cm of the no-till treatments [38]. As soil disturbance was more intensive in our study compared to the no-till treatments of Piegold et al [38], such clearly pronounced stratification could not occur.…”
Section: Meancontrasting
confidence: 79%
“…Other authors found, on the contrary, a clear stratification of P avail in no-till systems compared to inversion tillage with the highest values in the upper 5 cm of the no-till treatments [38]. As soil disturbance was more intensive in our study compared to the no-till treatments of Piegold et al [38], such clearly pronounced stratification could not occur. In addition, as the overall P status in the experimental area was high and very heterogeneous (Table 1), and as P is a rather immobile element, changes in the P status between the different tillage systems may not be visible even after 12 years of trial duration.…”
Section: Meancontrasting
confidence: 79%
“…Phosphorus fixed in soil was converted into various soil Pi fractions [ 44 ]. It has been well documented that the fractions of P in soil can greatly be dependent on soil types and the rates of P fertilizer.…”
Section: Discussionmentioning
confidence: 99%
“…The positive linear correlation of soil TIP concentration and P addition rates (Fig. S2) indicates that applied P was fixed mainly into inorganic forms (Chauhan et al, 1981) and converted to various soil P fractions (Piegholdt et al, 2013). Most of the applied P transformed into soil moderate-cycling IP fractions as seen from the decrease in the relative proportion of soil recalcitrant IP fractions (Fig.…”
Section: Effect Of P Additions Rates On Soil Ip Fractionsmentioning
confidence: 94%
“…The effect of combined N and P addition on ecosystem P dynamics may further depend on their relative amounts added to the soil. For instance, inorganic P solubility and availability were particularly large when P was applied with N (Ross et al, 1995), while N and P applied at higher N : P ratios increased plant P use efficiency and leaf phosphatase activity (Hogan et al, 2010). It is well known that variation in N : P input ratios can also alter plant litter N : P ratios (Vitousek et al, 2010;Güsewell, 2004;Sun et al, 2018), thereby further affecting N and P availability through litter decomposition.…”
Section: Introductionmentioning
confidence: 99%